2010
DOI: 10.1590/s1678-77572010000200004
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological assessment of predictors of caries increment in 7-10- year-olds: a 2-year cohort study

Abstract: ObjectiveThe aim of this 2-year cohort study (2003 to 2005) was to investigate how caries experience, at initial lesions (early or non-cavited lesions) and cavited stages, predicts caries increment in permanent teeth in 7-10- year-olds.Material and MethodsThe random sample of 765 children attending public schools in the city of Piracicaba, SP, Brazil, was divided into two groups: 423 children aged 7-8 years and 342 children aged 9-10 years. All subjects were examined by a calibrated examiner, using dental mirr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 22 publications
(26 reference statements)
4
20
1
2
Order By: Relevance
“…[4][5][6] Unfortunately, there is very little credible research based on longitudinal studies in this area to support current dental practice. A number of authors have published prediction models using generalized linear or logistic regression analysis to support their final explanatory model for caries presence.…”
Section: Caries Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] Unfortunately, there is very little credible research based on longitudinal studies in this area to support current dental practice. A number of authors have published prediction models using generalized linear or logistic regression analysis to support their final explanatory model for caries presence.…”
Section: Caries Predictionmentioning
confidence: 99%
“…[6][7][8][9][10][11] Relative risk of disease occurrence or absence over time is often quantified using a surrogate measure such as an odds ratio (OR). 5,[12][13][14][15] On the other hand, a statistical strength of association using sensitivity and specificity measures is often used to report an incremental change in caries over time. 6,16 Caries risk assessment Although dental caries has been termed a preventable and infectious disease for many years, the acceptance of preventive and corrective control strategies based on a medical model of disease management by the dental profession has been minimal to date.…”
Section: Caries Predictionmentioning
confidence: 99%
“…Além da experiência passada de cá-rie, lesões iniciais predizem o incremento de cárie em dentes permanentes em um período de dois anos 14 . A presença de biofilme e lesões de mancha branca foi identificada como preditor de risco para a cárie dental, tanto em crianças jovens 10 , quanto numa faixa etária mais avançada 11 .…”
Section: Discussionunclassified
“…Outro estudo mais recente, também realizado na cidade de Piracicaba, investigou como a experiência de cárie, em lesões iniciais e os estágios cavitados, predizem o incremento de cá-rie em dentes permanentes em um período de dois anos. Os autores concluíram que houve associação estatística entre lesão inicial e incremento de cárie na faixa etária de nove a dez anos e entre experiên-cia de cárie, tanto em dentes decíduos quanto em permanentes e o incremento de cárie 14 . Com relação à avaliação da influência dos defeitos de esmalte no desenvolvimento da cárie, um estudo longitudinal, do nascimento aos 36 meses, em crianças de baixo nível socioeconômico, residentes em João Pessoa -PB, avaliou essa associação 15 .…”
Section: Componentes Biológicosunclassified
“…Studies have indicated that initial carious lesions are significantly more prevalent than cavitated lesions 1,2 and that the presence of initial lesions is a predictor of caries increment in the permanent dentition. 3 Preventive strategies must be employed to revert the changes provoked by the disease in enamel through a noninvasive treatment. Topical fluoride has been used as an adjunct in the treatment of initial caries lesions.…”
Section: Introductionmentioning
confidence: 99%